The Use of Special Rehabilitative Exercises to Treat a Torn Ligament of the External Ankle Joint in Athletes - Shallal Mohammed, Wissam; Salah Mal Allah, Qusay; Hakim Waheed, Athar (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the study is to develop a set of rehabilitative exercises, especially those that are commensurate with the injury. The focus of the study for athletes in athletics may treat them and improve the condition of the joint and its return to its normal position. The research problem is to study the injury that occurs in the ankle joint, which is the tearing of its external ligaments, by putting a set of standardized exercises Which suits the type of injury with the use of a set of therapeutic methods to rehabilitate this injury among athletes in athletics, where the aim of the research is to identify the effect of exercise on the muscle strength working on the ankle joint, the range of motion and the degree of pain. As for the research methodology, the researcher used the experimental approach to suit the nature of the problem, which represents the research community and they are The players with torn external ligaments of the ankle joint within the Najaf governorate clubs in the jumping and jumping activities for athletics, which numbered (4) players. The researcher used tests of range of motion, strength and pain of the ankle joint. The duration of the rehabilitation program was 4 weeks, with 3 rehabilitative units per week. If the statistical bag (spss) was used to extract the results, they were discussed in a scientific and thoughtful manner supported by Arab and foreign sources. M appeared with a set of recommendations, including a clear improvement in range of motion, strength and degree of pain of the ankle joint resulting from rehabilitative exercises. In light of the conclusions, the researcher recommends paying attention to muscle strength and range of motion exercises in training units, which leads to protecting the player as much as possible from injuries. As well as attention to the rehabilitation period, which comes after the treatment period, due to its great importance in re-healing the injured part and returning to the stadiums as soon as possible.